Interprofessional survey on medication reconciliation activities in the US Department of Veterans' Affairs: development and validation of an Implementation Readiness Questionnaire. Issue 4 (13th October 2022) - Lesselroth, Blake; Church, Victoria Lee; Adams, Kathleen; Mixon, Amanda; Richmond-Aylor, Amy; Glasscock, Naomi; Wiedrick, Jack
Abstract : Background: Medication reconciliation (MR) can detect medication history discrepancies at interfaces-in-care and help avoid downstream adverse drug events. However, organisations have struggled to implement high-quality MR programmes. The literature has identified systems barriers, including technology capabilities and data interoperability. However, organisational culture as a root cause has been underexplored. Objectives: Our objectives were to develop an implementation readiness questionnaire and measure staff attitudes towards MR across a healthcare enterprise. Methods: We developed and distributed a questionnaire to 170 Veterans' Health Affairs (VHA) sites using Research Electronic Data Capture (REDCap) software. The questionnaire contained 21 Likert-scale items that measured three constructs, such as: (1) the extent that clinicians valued MR; (2) perceptions of workflow compatibility and (3) perceptions concerning organisational climate of implementation. Results: 8704 clinicians and staff responded to our questionnaire (142 of 170 VHA facilities). Most staff believed reconciling medications can improve medication safety (approximately 90% agreed it was 'important'). However, most (approximately 90%) also expressed concerns about changes to their workflow. One-third of respondents prioritised other duties over MR and reported barriers associated with implementation climate. Only 47% of respondents agreed they had enough resources to address discrepancies when identified. Interpretation: Our findings indicate that an MR readiness assessment can forecast challenges and inform development of a context-sensitive implementation bundle. Clinicians surveyed struggled with resources, technology challenges and implementation climate. A strong campaign should include clear leadership messaging, credible champions and resources to overcome technical challenges. Conclusions: This manuscript provides a method to conduct a readiness assessment and highlights the importance of organisational culture in an MR campaign. The data can help assess site or network readiness for an MR change management programme.